Perspektif Baru Metode Dan Aliran Tafsir Ibn Qayyim: Telaah Metode dan Aliran Tafsir at-Tibyan fi Aqsamil Qur’an - Muhaimin, Abdul; Munawaroh, Mas’ulil (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2019)
Qasam in the Koran shows the seriousness of Allah to convey material or strengthen arguments because of the lack of faith in the material delivered. This shows that knowing Qasam in the Qur'an is very urgent and it is not surprising if in the end Imam Ibn Qayyim al-Jauziyyah wrote a specific account explaining the Qasam in the Qur'an in his interpretation called “at-Tibyan fi Aqsamil Qur’an”. Therefore it is necessary to do a study to find out new perspectives of sources, methods and interpretations according to M. Ridlwan Nasir, thus adding insight into our study in the study of commentaries. The problem in this study is what sources, methods and interpretive flows are used in the tafsir “at-Tibyan fi Aqsamil Qur’an”. The results of the research that the research source used is bil Iqtiran (a combination of bil Ma'tsur and bil Ra'y), The method of the explanation uses the Bayan methodi , in terms of the breadth of the explanation using the Itnabi method , and seen from the goals & objectives of the verse interpreted using the Maudu'i method. While the flow / tendency, the flow Sufi, Lughawi, ‘Ilmi, and al-Fiqhi, but the most dominant flow is the Sufi.